Low temperature synthesis and electrical properties of PbTiO3 thin films prepared by the polymeric precursor method - Pontes, F. M.; Rangel, JHG; Leite, E. R.; Longo, Elson [UNESP]; Varela, José Arana [UNESP]; Araujo, E. B.; Eiras, J. A. (Elsevier B.V., 2000)
Ferroelectric PbTiO3 thin films were successfully prepared on a Pt(111)Ti/SiO2/Si(100) substrate for the first time by spin coating, using the polymeric precursor method. X-ray diffraction patterns of the films indicate that they are polycrystalline in nature. This method allows low temperature (500 degrees C) synthesis and high electrical properties. The multilayer PbTiO3 thin films were granular in structure with a grain size of approximately 110-120 nm. A 380-nm-thick film was obtained by carrying out four cycles of the spin-coating/heating process. Scanning electron microscopy (SEM) and atomic force microscopy (AFM) analyses showed the surface of these thin films to be smooth, dense and crack-free with low surface roughness (=3.4 nm). At room temperature and at a frequency of 100 kHz, the dielectric constant and the dissipation factor were, respectively, 570 and 0.016. The C-V characteristics of perovskite thin film prepared at low temperature show normal ferrolectric behavior. The remanent polarization and coercive field for the films deposited were 13.62 mu C/cm(2) and 121.43 kV/cm, respectively. The high electrical property values are attributed to the excellent microstrutural quality and chemical homogeneity of thin films obtained by the polymeric precursor method. (C) 2000 Elsevier B.V. S.A. All rights reserved.
Keywords: lead titanate; annealing; dielectric properties; ferroelectric and polymeric precursor